The Effect of Intraoperative Transversus Abdominis Plane Blocking on Postoperative Pain After Laparoscopic Transabdominal Pre-peritoneal (TAPP) Groin Hernia Repair - Chamzin, Alexandros; Frountzas, Maximos; Gkiokas, George; Kouskouni, Evaggelia; Xanthos, Theodoros; Michalopoulos, Nikolaos V. (Frontiers in Surgery, 2022)
Background: Managing postoperative pain even after laparoscopic groin hernia repair still remains an interesting challenge for clinicians especially for patients of high risk. Plenty of operative techniques and analgesic methods have been proposed in order to minimize postoperative pain after laparoscopic groin hernia repair. The aim of the present study is to compare transverse abdominis plane (TAP)-block with local analgesic infiltration at trocar entry sites in the terms of reducing postoperative pain. Methods: Patients that underwent laparoscopic trans-abdominal pre-peritoneal (TAPP) groin hernia repair in a high-volume university hospital were included. Patients were divided in two groups depending on the analgesic method used. Pain was assessed using Visual Numerical Scale (VNS) score. Results: Thirty patients were included. Intraoperative TAP-block seemed to be superior in terms of decreasing pain at the hernia area and at the trocar insertion site (p<0.05) compared to local analgesic infiltration at the trocar insertion site at 6, 12 and 24 hours after surgery (p<0.05). In addition, pain reduction was more effective in rest rather than in motion for both analgesic methods. Conclusion: Intraoperative TAP-block under direct vision seems to be an effective, fast and easy technique in order to reduce postoperative pain after laparoscopic groin hernia repair, but more studies are required to validate these results in a prospective and randomized context.